DEVELOPMENT OF SIGAPDESA INFORMATION SYSTEM FOR TRACKING CORRESPONDENCE STATUS IN KEMBIRITAN VILLAGE - Zanah, Aulia Miftahul; Ruth Ema Febrita; Rini, Eka Mistiko (Politeknik Negeri Banyuwangi Jl. Raya Jember km. 13 Labanasem, Kabat, Banyuwangi, Jawa Timur (68461) Telp. (0333) 636780, 2025)
Kembiritan Village, located in the Genteng District of Banyuwangi Regency, is one of the villages that has implemented the SmartKampung application for handling correspondence. However, the implementation of this application has not been optimal due to issues with the application not functioning properly. Another challenge is the lengthy process of submitting letters, often requiring residents to visit the village office in person to expedite the process. The development of the sigapDesa information system aims to design and build a web application that addresses these issues. This includes designing a user-friendly interface, developing a receipt feature for real-time tracking of the correspondence process, and enabling the downloading of letters in PDF format. The system will incorporate real-time receipt features, notifications via WhatsApp, and a PDF download function for the correspondence management system, using software testing mechanisms. The sigapDesa website is created using the RAD (Rapid Application Development) method, which involves stages of requirements planning, prototyping, testing, refining, development, and implementation. Through this website, residents can submit letters according to their needs, receive a tracking number to check the status of their letter submission, receive WhatsApp notifications once the letter is prepared by the admin or if the letter cannot be processed, and download the letter directly from the website in PDF format. In designing and building the real-time receipt feature, the author developed the generateToken() function, which aims to generate a CSRF token to be used in the security system.